Microelectronics sensor arrays with integral processing capability - Syarnsuddin, E.Y.; Hicks, Peter J. (Zielona Góra: Uniwersytet Zielonogórski)
A "smart" image sensor is described which is capable of performing low-level preprocessing of image data in parallel with the sensing operation. The chip consists of an array of 32 x 32 image sensing and storage cells and associated output circuits. The array is able to capture an image and simultaneously store the current and previous frames on separate capacitors located within each pixel site. Having the storage capacitors integrated into the sensing cells overcomes problems due to parasitic capacitance on the output lines which in turn improves the signal-to-noise ratio.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka